Rancang Bangun Sistem Informasi Komplain Pada PT. Adya Prima Kelola Berbasis Web - Dion Marusaha Gultom; Hany Maria Valentine; Iskandar Zulkarnain (FIKOM - Bung Karno University, 2022)
PT. Adya Prima manages buildings in Jakarta and other areas in Indonesia, one of which is The Lavende Residence Apartment. The existence of komplaints at The Lavende Residence Apartment which is managed by PT. Adya Prima is currently accepting komplaints from apartment residents through handling officers, so that residents need more time to complete the komplaint process. So, a web-based komplaint application was designed that can be used by residents to file complaints to find out the process, so that customers do not need to meet directly and the complaint process can be resolved. The complaint application is designed using UML (Unified Modeling Language) to help describe business processes as well as in making applications using the PHP and MySql programming languages.